The changing of oral argumentation process of grade XI students through Socratic dialogue - I W Pangestika; M Ramli; Nurmiyati Nurmiyati (Universitas Sebelas Maret, 2017)
Arguments are one of the important purposes in the modern era of learning because it is the basic step to promote student’s critical thinking process and science literacy. Argumentation process can be trained through interactive dialogue that provides opportunities for students to argue. This research aims to change oral argumentation process in biology class of high school through the application of the Socratic Dialogue. The participants were students of grade XI science in one high school located in Surakarta, selected purposively. A classroom action research was done collaboratively between student teacher, lecturers, and teacher, follow the spiral cycles of research by Stephen Kemmis. During the implementation of research, the audio recorder has prepared to record the dialogue and arguments of the students. Next, data recorded that was converted to a dialogue transcript analyzed qualitatively using the Toulmin Argumentation Patterns (TAP). Another data source is teacher’s reflective diaries that contained notes during the learning process. The result shows that student’s oral argumentation process found were only claiming supported by weak warrants. Implementation of the Socratic Dialogue brings positive changes in oral argumentation process of the students, proven by the complete argumentation pattern include claims, data, warrants, backings, and rebuttals at the end of the research cycle. A classroom action research which is developed collaboratively and implement interactive dialogue also inquiry learning is highly recommended to change student’s oral argumentation process.